Implementasi Perilaku Hidup Bersih dan Sehat Melalui Metode Pembiasaan di Masa Pandemi Covid-19 pada Anak Usia Dini - meyda setyana hutami (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
Covid-19 is a disease that is spreading very quickly right now. The disease not only attacks adults but can also occur in children. Strategies that can be used for PHBS programs are to wash your hands with soap and running water, use masks, and keep your distance. The method used in this study is a descriptive cauldron with data collection techniques through observation, interview, and documentation.Â  Based on the research concluded that children are very enthusiastic about the phbs program by getting used to hand washing with soap, using masks, and keeping distance from the crowd.